Behavioural interventions for weight management in pregnancy: A systematic review of quantitative and qualitative data - Campbell, Fiona; Johnson, Maxine; Messina, Josie; Guillaume, Louise; Goyder, Elizabeth (BMC public health, 2011)
Background There is a rising prevalence of excessive weight gain in pregnancy and an increasing number of pregnant women who are overweight or obese at the start of the pregnancy. Excessive weight gain during pregnancy is associated with adverse maternal and neonatal consequences and increases the risk of long-term obesity. Pregnancy therefore may be a key time to prevent excessive weight gain and improve the health of women and their unborn child. This systematic review sought to assess the effectiveness of behavioural interventions to prevent excessive weight gain in pregnancy and explore the factors that influence intervention effectiveness. Methods We undertook a systematic review of quantitative and qualitative evidence. This included a meta-analysis of controlled trials of diet and physical activity interventions to prevent excessive weight gain during pregnancy and a thematic synthesis of qualitative studies that investigated the views of women on weight management during pregnancy. A thorough search of eleven electronic bibliographic databases, reference lists of included studies, relevant review articles and experts in the field were contacted to identify potentially relevant studies. Two independent reviewers extracted data. RevMan software was used to perform the meta-analyses. Qualitative data was subject to thematic analysis. Both quantitative and qualitative data were aligned using a matrix framework. Results Five controlled trials and eight qualitative studies were included. The overall pooled effect size found no significant difference in gestational weight gain amongst participants in the intervention group compared with the control group (mean difference -0.28 95% CI -0.64 to 0.09). The study designs, participants and interventions all varied markedly and there was significant heterogeneity within this comparison in the meta-analysis (I 2 67%). Subgroup and sensitivity analysis did not identify contextual elements that influenced the effectiveness of the intervention. In a thematic analysis of the qualitative studies, three major themes emerged relating to women's views of weight management in pregnancy: pregnancy as a time of transition and change, conflicting and contradictory messages and a perceived lack of control. When the results of both quantitative and qualitative data were aligned it was clear that some of the barriers that women described in achieving healthy weight gain in pregnancy were not addressed by the interventions evaluated. This may have contributed to the limited effectiveness of the interventions. Conclusions Despite intense and often tailored interventions there was no statistically significant effect on weight gain during pregnancy. Inadequate and often contradictory information regarding healthy weight management was reported by women in qualitative studies and this was addressed in the interventions but this in itself was insufficient to lead to reduced weight gain. Multiple types of interventions, including community based strategies are needed to address this complex health problem.